Sensitivity of Biochemical and Imaging Findings for the Diagnosis of Acute Pancreatitis in Children - Orkin, Sarah H. (J Pediatr, 2019)
OBJECTIVE: To determine diagnostic sensitivity of serum biomarkers and imaging in diagnosis of acute pancreatitis (AP) in children. STUDY DESIGN: Cross-sectional analysis of prospective registry data for children (age <21-years) whose first documented attack of AP occurred between March 2013 - October 2016 at a single institution, tertiary care center. Main outcome was sensitivity of serum biomarkers and of imaging modalities, measured via descriptive statistics. RESULTS: 112 children met criteria for AP, 57 (51%) were male with a median age of 13.4 years (interquartile range: 9.3-15.8 years). Serum Amylase and lipase levels were obtained in 85 (76%) and 112 (100%) patients, respectively. Imaging was performed in 98 (88%) patients with abdominal ultrasound (US) performed in 84 (75%) and CT and/or MRI performed in 46 (41%) patients. Fifty-three (47%) patients met all three diagnostic criteria (clinical, biochemical and imaging) for AP. Laboratory testing had a 5.4% false negative rate for AP. Serum lipase alone and amylase alone were 95% (95% CI: 89-98%) and 39% (95% CI: 28-50%) sensitive for AP, respectively. Imaging (any modality) was 61% sensitive (95% CI: 51-71%) for AP with a 34% false negative rate. US alone was 52% (95% CI: 41-63%) sensitive for AP and CT/MRI was 78% (95% CI: 63-89%) sensitive. Combinations of diagnostic criteria performed no better than laboratory testing alone. CONCLUSIONS: The majority of children coming to medical attention with their first documented occurrence of AP have characteristic symptoms. Serum lipase is highly sensitive for the diagnosis of AP, and serum amylase is moderately sensitive. Imaging, particularly US, is only moderately sensitive and cross-sectional imaging provides higher sensitivity for diagnosing AP.